Pengembangan Bahan Ajar Buku Rukun Iman pada Mata Pelajaran Akidah Akhlak di MIS NU Kota Palangkaraya - Muhammad Syabrina; Yuli Triani; Yuliana Yuliana; Raudlatul Jannah (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The purpose of this study is to develop teaching materials in the form of interactive textbooks on the subject of Rukun Iman (the Five Pillars of Islam) for MIS NU students in Palangkaraya City. The motive for this study is the need for more contextual and relevant teaching resources on Aqidah Akhlak (Islamic beliefs and morals) in order to optimize students' understanding. The ADDIE development model, which includes the phases of needs analysis, product design, development, implementation, and evaluation, was used in this study. Validation was carried out by subject matter experts, design experts, and educators as practitioners to ensure the suitability of the product. Based on the validation results, subject matter experts and designers consistently rated the teaching materials as “very feasible” in terms of media functionality, visual appeal, and material completeness. Improved learning outcomes through pre- and post-tests, as well as a feasibility rate of 93.02%, were demonstrated during implementation in a field test with 30 second-grade students. Moderate to significant learning gains were shown by N-Gain analysis. The findings prove the effectiveness of interactive learning books in improving students' understanding of the Five Pillars of Islam and providing alternative teaching resources that are more interesting and easier to understand. It is hoped that this publication will serve as a guide for educators in Islamic elementary schools to maximize the teaching of Aqidah Akhlak.